Encouraging Paternity Leave to Bridge Gender Discrimination in Employment Opportunities: A Sri Lankan Perspective - Mathuri, K. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and surana International Attorneys India, 2025)
The reduced rate of women in employment is influenced by various factors, including social and cultural norms, family responsibilities, discriminatory hiring practices, workplace challenges, and safety concerns. This paper focuses on the connection between maternity leave and discriminatory hiring practices, which significantly hinder women’s employment opportunities. Despite Sri Lanka's comprehensive labour laws, the legal system continues to perpetuate gender-discriminatory practices, such as the absence of paternity leave. While this gap may seem to disadvantage men, it primarily reflects entrenched societal ideologies that view women as the primary caregivers. This belief reinforces hiring biases, as employers may hesitate to employ women due to potential maternity-related absences, further exacerbating barriers to women's employment. The paper argues that introducing paternity leave would promote equitable childcare responsibilities between parents, challenging outdated gender norms and reducing the undue burden placed on women. By fostering a gender-equal parental leave policy, such reforms could enhance women’s employment opportunities and advance workplace gender equality. The analysis critically evaluates Sri Lanka's labour laws on parental leave, international standards, and the country's obligations to them, while drawing on global best practices. The paper ultimately recommends legislative and policy reforms to address these gaps, aligning Sri Lanka with international commitments and fostering a more inclusive workforce.
Keywords: Gender discrimination; Employment opportunities; Hiring practices; Maternity leave; Paternity leave